2017
DOI: 10.3390/molecules23010015
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Compounds in Brassicaceae Vegetables with a Role in the Prevention of Chronic Diseases

Abstract: The beneficial role of the Mediterranean diet in the prevention of chronic diseases, including cardiovascular diseases, diabetes, and obesity, is well-recognized. In this context, Brassicaceae are considered important vegetables due to several evidences of their health promoting effects that are associated to bioactive compounds present in the edible parts of the plants. In this review, the mechanisms of action and the factors regulating the levels of the bioactive compounds in Brassicaceae have been discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(83 citation statements)
references
References 64 publications
1
80
0
2
Order By: Relevance
“…Phytochemical screening results of broccoli extract indicate that positive broccoli plants contain alkaloids, saponins, tannins, and flavonoids. These results are in line with several previous studies which showed the existence of the compound class (Chauhan et al, 2016;Hussain et al, 2019;Mageney et al, 2017;Raiola et al, 2017). The complete phytochemical screening results are presented in Table I.…”
Section: Phytochemical Screeningsupporting
confidence: 91%
“…Phytochemical screening results of broccoli extract indicate that positive broccoli plants contain alkaloids, saponins, tannins, and flavonoids. These results are in line with several previous studies which showed the existence of the compound class (Chauhan et al, 2016;Hussain et al, 2019;Mageney et al, 2017;Raiola et al, 2017). The complete phytochemical screening results are presented in Table I.…”
Section: Phytochemical Screeningsupporting
confidence: 91%
“…In connection to this, the gut microbiota has been shown to be altered by consumption of dietary fiber rich cruciferous vegetable, such as broccoli, cauliflower and cabbage, which could ultimately influence gut metabolism of bioactive food components and host exposure to these beneficial compounds [73]. Phenolic compounds in themselves have been shown to be beneficial for health, e.g., by increasing weight loss in obese mice and humans [74], and also to lower the mortality of some chronic diseases, mainly cardiovascular diseases and cancer [75].…”
Section: Discussionmentioning
confidence: 99%
“…[72]. Among the phytochemicals studied, a special attention has been paid on phenolic compounds from a variety of sources [73,74], such as tea [75,76], grapes [77], ginseng [78], red to purple colour fruits [79][80][81], cruciferous vegetables [82,83], etc. Several bioactive compounds found in oils, such as tocopherols and tocotrienols, phenolic acids, flavonoids, and sterols have anti-obesity effects [84].…”
Section: Obesitymentioning
confidence: 99%